Understanding cost and pricing: The perception of women entrepreneurs - Santos, José Glauber Cavalcante dos; Alves, Thífane Teixeira (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: In any variety of business, the aspects of prior knowledge, planning, organization and adopted strategies are considered decisive for growth. In women's businesses, this becomes even more important, because women face additional challenges in their businesses compared to men. Purpose: The research aims to understand the perception of the cost concept and the adoption of pricing strategies from the perspective of entrepreneurial women. No studies are found in the literature that took on these combined problems. Method: The study is classified as exploratory-descriptive, with a qualitative and multi-case approach. The investigation heard 14 women entrepreneurs from the city of Fortaleza/CE. Structured Interviews were carried out and the technique of categorical content analysis was applied to deal with the manifestations of the interviewees after the process of transcription of the speeches. Results: There is a limited understanding of what is defined as cost, regardless of education, but close to the accounting mainstream. Price has cost and market as antecedents. Despite listing gender barriers, the interviewees do not recognize/perceive these difficulties. This research indicates areas and actions on which professional training policies for women can focus. Moreover, this paper highlights the social restrictions that impede female professional development, as many of the interviewees do not perceive such barriers. Conclusions: It is concluded that women face specific difficulties in conducting and developing businesses, which imposes a competitive disadvantage on their ventures and increases the chance of failure and withdrawal. Despite this, the results show that, with adequate encouragement, women entrepreneurs can improve and consolidate their practical knowledge about establishing the cost of products/services and improve the pricing strategies learned, often through practical experience. This would reduce the social distance between men and women in the field of entrepreneurship.